Papua New Guinea : Staff Report for the 2000 Article IV Consultation and First Review Under the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Papua New Guinea showed satisfactory performance under the Stand-By Arrangement. Executive Directors commended the macroeconomic stabilization and structural reform, and emphasized the need to maintain fiscal and monetary stances. They appreciated the improved governance, transparency, and efficiency of the public sector, as indicated by the recent assessment of Papua New Guinea's observance of the code on fiscal transparency. They indicated the need to strengthen the technical and managerial capacity of the National Statistical Office, and noted the potential role of technical assistance in improving statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet